Experiences of Individuals Living With Diabetic Foot Ulcers at the Korle- Bu Teaching Hospital - Salia, V.O.A (My University, 2014)
Globally, 382 million people live with Diabetic Mellitus (DM). Diabetic foot ulcer is a major complication of diabetes characterized by the triad of neuropathy, infection and ischaemia. It affects 15-20% of the people diagnosed with diabetes in their live time. The disease accounts for up to 10% of non-traumatic limb amputation. Using an exploratory descriptive design, the purpose of this study was to explore the experiences of diabetic patients living with foot ulcers. Purposive sampling was used to recruit 12 participants from Korle-Bu Teaching Hospital in Accra, Ghana (KBTH). In-depth interviews were conducted using a semi structured interview guide. Data was analysed using Miles and Huberman content analysis. Four major themes being participants‘ knowledge regarding diabetic foot ulcer, challenges of managing diabetic foot ulcers, coping strategies in managing diabetic foot ulcers, and support systems in managing diabetic foot ulcers emerged from the study. In conclusion, education on foot care practices must be intensified by healthcare professionals to enable patients self- manage the ulcer. Provision of emotional, social and psychological support to patients managing diabetic foot ulcers must be made a priority to help them cope with the effects of the foot ulcers. Further research in assessing foot care practices among diabetic patients and identifying determinants of these practises is vital in improving patients‘ quality of life. Additionally, it may be imperative to conduct this study at multiple sites for generalization of findings.
Thesis (MPhil) - University of Ghana,2014